Fostering Ecological Awareness: A Mulimodal Discourse Analysis of From This Island Advertisment: - Ukhti Jihan Humaira; Muhammad Hafiz Kurniawan (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The skincare industry is experiencing rapid growth, which has sparked increased competition among brands. However, as times change and the beauty industry introduces a wide range of new innovations, many brands are launching products made from natural ingredients—a move seen as a demonstration of their commitment to the environment. From This Island is a local Indonesian skincare brand that consistently raises issues of sustainability and nature conservation in its advertisements. This study aims to how analyze ecological awareness is fostered in the “From This Island” advertisement through a multimodal discourse analysis framework. This study uses a descriptive qualitative approach with data in the form of digital advertisements published on the brand’s official platform. The results of the study show that this commercial successfully raises ecological consciousness by combining sustainability-focused discourse with images that highlight harmony, natural beauty, and environmental care. Nature is shown as an entity that requires care and protection rather than just as a resource. A compelling ecological narrative that may capture both the audience’s cognitive and emotional reactions is created by this blending of spoken and visual components. Additionally, by encouraging responsible consumption and highlighting pro-environmental principles, the campaign represents a wider ecological discourse. This study shows that ads can be used as a strategy for support for the environment in addition to being a commercial medium.